ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PENYALURAN KREDIT UMKM (Studi Pada Bank Umum yang Terdaftar di Bursa Efek Indonesia Periode 2009-2013) - Nurlestari, Annisa; Mahfud, M. Kholiq (Diponegoro Journal of Management, 2015)
The purpose of this research is to examine the influence of Capital Adequacy Ratio (CAR), Third-Party Funds (TPF), Non-Performing Loan (NPL), Interest Spread and Return On Assets (ROA) to distribution of credit of SME in commercial bank. This research used the Commercial Bank which was listed it to Indonesian Stock Exchange. The data that it used at this research came from the annual published financial report of each Commercial Banks.             The population in this research was all Commercial Banks that was listed it to Indonesian Stock Exchange during period 2009 through 2013. The amount of population was 32 commercial banks. After passed the purposive sampling method, amount of the bank that fulfilled the criteria of sample became 11 commercial banks. The method that used in this research was multiple regression analysis and then used assumption classic test and used hypothesis test that including F-statistic, T-statistic and determination of coefficients (R2).            The result of this research was CAR variable influence negatively and significant to distribution of SME’s credit, ROA variable influence negatively and significant to distribution of SME’s credit and DPK and NPL variable influence positively and not significant to distribution of SME’s credit. Interest spread variable influence negatively and not significant to distribution of SME’s credit.